Experimental Investigation of Concrete using m Sand as a Replacement of Natural Sand and Utilization of Fibers in Concrete - Thakre, Praveen Kumar; Raj, Ravindra (International Journal of Scientific Research in Civil Engineering, 2022)
Concrete has become an essential element of the building business as a result of its enhanced nature and better assessment of coarse totals, and the ingredients used to create cement have progressed. Sand is an essential component of cement. It is mostly derived from traditional sources. As a result, we have little control over sand assessment.The M-25 evaluation solid blocks were thrown into the present research work, and efforts were made to deconstruct numerous solid features of concrete, Proposal of the study is to determine the advantageous results of sand (manufacturing) in construction industry if replacing natural sand. For this we are proposing experimental study where its utility is observed. We are preparing samples with replacing percentage of 50%, 70% and 90% by weight and including fiber (bamboo) by 5%. The general properties of fresh and solidified cement are now being examined, and the findings are being deconstructed. In the building business, concrete is a vital material. Currently, it can be shown that M-sand greatly boosted the compressive strength of high-quality cement. Bamboo fiber contributes in the enhancement of solid properties, enabling you to avoid breakage and disappointment.For 28 days of curing, we raised the amount of M-sand to 50 percent, 70 percent, and 90 percent compressive quality increments of 25.1, 26.4, and 27 N/mm2, Flexural strength increments of 5.5, 7.02, and 12.9 N/mm2 during 28 days of curing, the beam's flexural strength improved as well.
Keywords: Concrete; M Sand; Natural Sand; Fibers; Compression; Tensle